2006
DOI: 10.1063/1.2172909
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical properties of group-IV ferromagnetic semiconductor Ge1−xFex grown by low-temperature molecular beam epitaxy

Abstract: A new group-IV ferromagnetic semiconductor, Ge 1-x Fe x , was successfully grown by low-temperature molecular beam epitaxy (LT-MBE) without precipitation of ferromagnetic Ge-Fe intermetallic compounds. The ferromagnetism of Ge 1-x Fe x films was investigated by magnetic circular dichroism (MCD). In particular, the influence of the Fe content (F Fe /F Ge =1 -10%) and growth temperature (100, 200 O C) on the ferromagnetism was carefully studied. The MCD measurements revealed that the band structure of the Ge 1-x… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 20 publications
3
29
0
Order By: Relevance
“…The Ge 1-x Fe x films grown at T S = 100 and 200 °C showed 2-dimensional growth mode and exhibited diamond-type crystal structure with single phase. This result was consistent with our TEM observation [20]. Note that in our previous paper, it was found using TEM and spatially resolved energy dispersive X-ray spectroscopy (EDX) that the 200 °C-grown Ge 1-x Fe x film exhibited diamond-type crystal structure including slightly nonuniform Fe distribution and tiny stacking fault defects in the epitaxial layer.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The Ge 1-x Fe x films grown at T S = 100 and 200 °C showed 2-dimensional growth mode and exhibited diamond-type crystal structure with single phase. This result was consistent with our TEM observation [20]. Note that in our previous paper, it was found using TEM and spatially resolved energy dispersive X-ray spectroscopy (EDX) that the 200 °C-grown Ge 1-x Fe x film exhibited diamond-type crystal structure including slightly nonuniform Fe distribution and tiny stacking fault defects in the epitaxial layer.…”
supporting
confidence: 93%
“…Thus, the formation of ferromagnetic precipitates in the film was ruled out. The Curie temperature (T C ) evaluated from the Arrott plots of the MCD hysteresis loops linearly increased with increasing Fe content (x) up to 17.5% [20]. Thus, we concluded that the Ge 1-x Fe x thin films are characterized as an "intrinsic" ferromagnetic semiconductor.…”
mentioning
confidence: 90%
“…3,4,5,6 In this paper, we present the growth temperature (T S ) dependence of T C and the lattice constant of GeFe, that are investigated by magnetic circular dichroism (MCD) and the X-ray diffraction (XRD) measurements.…”
Section: Introductionmentioning
confidence: 99%
“…6 In the case of Ge 1-x Fe x films, we can grow single-crystal films of a diamond type with the non-uniform distribution of Fe atoms without any intermetallic Fe-Ge compounds, which is appropriate for heterostructure applications, but the current problem of GeFe is its low Curie temperature (T C ) which is at the highest 170 K so far. [7][8][9] Recently, however, GeFe quantum dots with a high T C of ~400 K without any observable precipitates have been reported. 10 Thus, if we can grow GeFe quantum dots (or nano-particles) inside a Ge film with a flat surface or interfaces with other layers (or substrates), they are very promising.…”
mentioning
confidence: 99%